The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fpls.2016.01693
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the Tubby-Like Protein Family in the Malus domestica Genome

Abstract: Tubby-like proteins (TLPs), which have a highly conserved β barrel tubby domain, have been found to be associated with some animal-specific characteristics. In the plant kingdom, more than 10 TLP family members were identified in Arabidopsis, rice and maize, and they were found to be involved in responses to stress. The publication of the apple genome makes it feasible to systematically study the TLP family in apple. In this investigation, nine TLP encoding genes (TLPs for short) were identified. When combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 63 publications
5
37
0
Order By: Relevance
“…Based on the analysis of the typical domains and gene structure of TLPs, we found that all TLPs expect TLP11 contain both the Tub domain and F-box domain, which is consistent with previous reports that most plant TLPs contain the F-box domain [2,4,6,7]. Moreover, we found that the motifs in TLP2 are different from other TLPs (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Based on the analysis of the typical domains and gene structure of TLPs, we found that all TLPs expect TLP11 contain both the Tub domain and F-box domain, which is consistent with previous reports that most plant TLPs contain the F-box domain [2,4,6,7]. Moreover, we found that the motifs in TLP2 are different from other TLPs (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, most TLP promoters contained both CGTCA-motif and TGACG-motif which were related to the jasmonate acid response. Moreover, ARE, which was related to anaerobic reaction and ABRE, which was associated to the abscisic acid response, were found in most TLPs' promoters [2,4,6,15]. These results suggest that TLPs may play an important role in stress response, but this needs further experimental verification.…”
Section: Analysis Of Promoter Sequences Of Sltlpsmentioning
confidence: 88%
See 2 more Smart Citations
“…Apple ( Malus domestica ) is an important commercial fruit crop, and its production is highly affected by environmental factors, especially light [ 29 , 30 ]. PIFs play a central role in adapting plants to different light conditions; however, identification and functional analysis of PIFs in apples have not been systematically investigated, except MdPIF1 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%